MEDIA PHOTOVOICE UNTUK MENGGAMBARKAN PEMBINAAN KEAGAMAAN SĂMAŅERA DAN AṬṬHASĪLANĪ PADEPOKAN DHAMMADĪPA ĂRĂMA - Riawati Riawati (Jurnal Agama Buddha dan Ilmu Pengetahuan, 2021)
This study aims to find out how Photovoice media can provide an overview of the religious formation carried out by sāmaṇera and aṭṭhasīlanī Padepokan Dhammadīpa rāma. This research is a qualitative research using the Photovoice method. The data collection techniques in this study were observation, documentation, interviews, and the use of individual experience data. The results of the research of sāmaṇera and aṭṭhasīlanī Padepokan Dhammadīpa rāma when they have semester breaks not only stay at the monastery, but they also provide guidance to people in various cities in Indonesia. Examples of coaching the people, coaching anjangsana, fostering Buddhist Sunday Schools, coaching sports, filling out the Dhammadesana, and being a religious tour guide at the Dhammadīpa Rāma Padepokan Vihara. In addition, the coaching that is carried out alone is carrying out worship services, activities carried out through training, training activities to convey Dhammadesa and participating in interfaith activities. This can be known or proven through pictures or photos.